Chemical and biological characterization of the Salinas of the parish of Santa Catalina, province of Imbabura – Ecuador - González Flores, Jazmín Alexandra (2021)
This study examines mountain salt, which has been a valuable commodity since pre-Columbian times due to its rarity and high iodine concentration. In Santa Catalina of Salinas-Ibarra, it gives from of salt extraction process, a by-product has originated, for some time. People in this sector recognize this liniment as an ionized solution. This solution is dark brown and turns oily after sitting for about seven months. The inhabitants of Santa Catalina de Salinas-Ibarra, use liniment as an anti-inflammatory and antiseptic; the latter is applied after mosquito bites. As a result, the goal of this research is to get a preliminary characterization of the liniment and the tolas samples which have hygroscopic characteristics. To make the study easier the tolas were split into three sections: top, middle, and base, similar to how the liniment was divided. This first approach was achieved through a comprehensive process that included (1) extracting the polar and non-polar fractions of the samples, (2) mineralogical assessment and semi-quantitative study of the compounds using an XRD-diffractor and SEM, and (3) antibacterial activity using the agar diffusion test or Kirby-Bauer test technique. This study seeks to enhance local capacities in addition to supporting this empirical knowledge with scientific contributions.